Women and the risk of Alzheimer's disease - O’Neal, Mary A. (Frontiers in Global Women's Health, 2024)
Purpose of the review This review will elucidate reasons to explain why women may be at greater risk for Alzheimer's disease. Recent findings Potential mechanisms to explain sex and gender differences in Alzheimer dementia include: differences in risk associated with the apolipoprotein E 4 allele; telomere shortening- which is linked with neurodegeneration, higher incidence of depression and insomnia in women as psychiatric co-morbidities which are linked with an increased Alzheimer disease risk, disorders of pregnancy including gestational hypertension and preeclampsia and psychosocial factors such as educational level which may contribute to differences in cognitive reserve. Summary The sex and gender differences in Alzheimer's disease can be explained by biological and psychosocial factors.